ANALISIS WACANA KRITIS (TEORI VAN DIJK DALAM KAJIAN TEKS MEDIA MASSA) - Kuntoro, Kuntoro (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Critical discourse analysis put its emphasis on the power constellation involved in the meaning production and reproduction process. An individual is not viewed as a neutral subject who has a capability to interpret the meaning freely. He or she is a social subject having a relation with others and an object to the influence of social power exist in a society. This article tries to explore and apply Van Dijk theory of critical discourse analysis in the news of the printed media.